Risk factors for fluoropyrimidine-induced cardiotoxicity in colorectal cancer: A retrospective cohort study and establishment of a prediction nomogram for 5-FU induced cardiotoxicity - Wang, Yan; Wang, Wenling; Dong, Hongming; Wang, Gang; Chen, Wanghua; Chen, Juan; Chen, Weiwei (Frontiers in Oncology, 2023)
Fluoropyrimidine is an important component of systemic chemotherapy for colorectal cancer (CRC). Fluoropyrimidine-induced cardiotoxicity (FIC) may result in delay and discontinuation of chemotherapy and, in severe cases, can even be life-threatening. To date, risk factors for FIC have not been well identified. This cohort study aimed to identify the predictors of FIC in CRC patients and develop a risk prediction nomogram model.A total of 916 patients were included for analysis, and 200 (21.8%) experienced FIC. LASSO algorithm and multivariate logistic regression analysis presented that chemotherapy ≤ 3 cycles (OR=4.694, 95% CI=3.184-6.92), age≥ 60 (OR=1.678, 95% CI=1.143-2.464), BMI 22.97 (OR=1.77, 95% CI=1.202-2.606), and simultaneous use of bevacizumab (OR=2.922，95% CI=1.835-4.653) were significant risk factors,and included in the prediction model for 5-Fu induced cardiotoxicity. The C-index (95% CI) was 0.751 (0.706-0.795) by internal validation. For patients treated with capecitabine-based regimen, the incidence of FIC increased with the absolute value of neutrophils (OR=5.177，95% CI=1.684-15.549) and eosinophils (OR=3.377，95% CI=1.237-9.22). Our study identified risk factors for FIC and established a prediction nomogram model based on chemotherapy cycle, age, BMI and use of target therapy for 5-FU induced Cardiotoxicity. The discriminative prediction model can be used for patient counselling and risk-stratification before undergoing chemotherapy in colorectal cancer.